Wealth Creation through Service Innovation Design in Malaysia - Rahman, Khairul Aidil Azlin Abd; Majid, Ahmad Zuhairi Abdul; Shaari , Nazlina (2010)
Innovation serves as a competitive advantage that allows company to dominate a particular market segments. Innovation is the key in extending market share but also to increase commercial gains. The key to innovation are not only market and technology but service innovation design. The changes of innovation design from functional design are to fulfilling the physical needs and feeling design to fulfill the experience needs. However, service innovation design is to fulfilling the integrity needs that enable consumer to enjoy the services that are important in their lives. The service industry is highly regional in nature; it should be framed in relation to regional revitalization as well. The service industry is important in that it creates employment for the region while at the same time increasing the region’s brand power. This paper will present a conceptual frame work of service innovation design in Malaysia.